2012
DOI: 10.1186/1744-9081-8-56
|View full text |Cite
|
Sign up to set email alerts
|

Marine omega-3 polyunsaturated fatty acids induce sex-specific changes in reinforcer-controlled behaviour and neurotransmitter metabolism in a spontaneously hypertensive rat model of ADHD

Abstract: BackgroundPrevious reports suggest that omega-3 (n-3) polyunsaturated fatty acids (PUFA) supplements may reduce ADHD-like behaviour. Our aim was to investigate potential effects of n-3 PUFA supplementation in an animal model of ADHD.MethodsWe used spontaneously hypertensive rats (SHR). SHR dams were given n-3 PUFA (EPA and DHA)-enriched feed (n-6/n-3 of 1:2.7) during pregnancy, with their offspring continuing on this diet until sacrificed. The SHR controls and Wistar Kyoto (WKY) control rats were given control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…Indeed, the ratios were strongly enhanced following exposure to PCB 153 in both male and female WKY as well as in male SHR, but no effects occurred in the female SHRs, indicating that the female SHR may represent a unique neurobiological phenotype regarding PCB exposure. In contrast, no changes were seen in the levels or dynamics of the measured amino acid transmitters (Dervola et al, 2012).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Indeed, the ratios were strongly enhanced following exposure to PCB 153 in both male and female WKY as well as in male SHR, but no effects occurred in the female SHRs, indicating that the female SHR may represent a unique neurobiological phenotype regarding PCB exposure. In contrast, no changes were seen in the levels or dynamics of the measured amino acid transmitters (Dervola et al, 2012).…”
Section: Discussionmentioning
confidence: 77%
“…No significant changes occurred in either the levels (nmol/mg protein) or the turnover of the neurotransmitter amino acid levels (Dervola et al, 2012) between the genotypes or after exposure to PCB 153 (Table 1).…”
Section: Amino Acidsmentioning
confidence: 96%
See 1 more Smart Citation
“…A fish oil enriched diet was reported to reduce ambulatory activity in Wistar rats [28]. In SHRs, dams were given n-3 PUFA-enriched feed during pregnancy and their offspring continued on this diet [29]. This study showed an n-3 PUFA-induced reduction in spontaneous locomotion.…”
Section: Discussionmentioning
confidence: 67%
“…Both of these results might me due to the fact that this group had maximum number of study as well as control subjects. Dervola et al, reported sex-specific changes in rat models of ADHD (more improvement in male rats) and attributed it to changes in presynaptic striatal monoamine and amino acid signaling [25].…”
Section: Discussionmentioning
confidence: 99%